(untitled) (Research, Society and Development, 2026)
Introduction: Acute Chagas Disease (ACD) remains a significant public health issue in Brazil, with notable changes in its epidemiological profile over recent decades. Aim: This study aimed to critically analyze transmission patterns, geographic distribution, and clinical outcomes of ACD in the country. Methods: This is an integrative literature review with a descriptive and exploratory approach, based on studies published between 1991 and 2024 in PubMed, SciELO, and LILACS databases. Original studies, case reports, and case series describing laboratory-confirmed ACD cases in Brazil were included. Results: The findings demonstrate a reconfiguration of the disease’s epidemiological profile, with a growing predominance of oral transmission, particularly associated with the consumption of contaminated foods such as açaí and sugarcane juice, and a strong concentration of cases in the Northern region, especially in the state of Pará. Additionally, a geographic expansion to previously non-endemic areas and considerable variability in outbreak magnitude were observed. Clinically, the disease is characterized by nonspecific initial manifestations and a risk of severe complications, particularly cardiac involvement, associated with higher parasitic load. Conclusion: In conclusion, ACD in Brazil presents a dynamic and multifactorial pattern, requiring strengthened epidemiological surveillance strategies, with emphasis on food safety, early outbreak detection, and healthcare professional training.